SEEG in 3D: Interictal Source Localization From Intracerebral Recordings - Satzer, David; Esengul, Yasar T.; Warnke, Peter C.; Issa, Naoum P.; Nordli, Douglas R. (Frontiers in Neurology, 2022)
Background: Stereo-electroencephalography (SEEG) uses a three-dimensional configuration of depth electrodes to localize epileptiform activity, but traditional analysis of SEEG is spatially restricted to the point locations of the electrode contacts. Interpolation of brain activity between contacts might allow for three-dimensional representation of epileptiform activity and avoid pitfalls of SEEG interpretation. Objective: The goal of this study was to validate SEEG-based interictal source localization and assess the ability of this technique to monitor far-field activity in non-implanted brain regions. Methods: Interictal epileptiform discharges were identified on SEEG in 26 patients who underwent resection, ablation, or disconnection of the suspected epileptogenic zone. Equivalent current dipoles and current density were calculated using a finite element head model. Surgical treatment volume (TV) and postoperative seizure freedom were used to assess the validity of source localization results. Results: The proportion of current within the TV was greater in seizure-free patients (P=0.04) and was able to predict surgical outcome with 45% sensitivity, 93% specificity, and 73% accuracy. Addition of scalp EEG led to more superficial modeled sources (P=0.03) and negated the ability to predict seizure outcome (P=0.23). Removal of near-field data from contacts within the TV resulted in smearing of the current distribution (P=0.007) and precluded prediction of seizure freedom (P=0.20). Conclusions: Interictal source localization with SEEG can distinguish between seizure-free and non-seizure free patients with reasonable accuracy if near-field recordings are obtained from the surgical target. SEEG-based interictal source localization is useful in illustrating and corroborating the epileptogenic zone. Additional techniques are needed to localize far-field epileptiform activity from non-implanted brain regions.